Інноваційна культура сучасного підприємства - Погорєлова, Тетяна Олексіївна; Колотюк, Олена Іванівна; Шевченко, А. С. (НТУ "ХПІ", 2014)
У статті розглянуто проблеми ефективності інноваційної діяльності, яка залежить від її організації, інтелектуального й інноваційного потенціалу підприємства, а значною мірою від стилю керівництва. Поняття інноваційної культури, яке розглядається як цілісна система вироблених в організації, і притаманних її членам моделей поведінки, що впливають на модус, спосіб життєдіяльності організації. Забезпечення, інноваційним потенціалом, конкурентоспроможності підприємства, та залежність стимулювання його розвитку від інноваційної культури.

The article considers problems of innovation performance, the effectiveness of innovation depends on the intellectual and innovative potential of the enterprise and very dependent on the leadership style. Innovation culture is a system of behavior it affects the activities of the organization Innovative potential provides enterprise competitiveness, encourage the development of enterprises depends on the innovation culture. Describes the corporate culture. Corporate culture consists of the potential of each employee, which gives it a good value, much more efficient use of human resources. Man - the main reference point of properly formed culture. Opportunities and business qualities of the person getting better thanks to the corporate culture, is its main purpose and guarantee the success of the company. Innovation culture helps to accept new ideas, support and implement them. for the successful implementation of innovative development strategy, managers should pay attention to the formation of corporate culture. Useful to adhere to the rules of corporate culture.
Innovation culture of modern enterprise
Keywords: інноваційна діяльність; формування; розвиток; інноваційний потенціал; innovation culture; innovative activities; ormation; development; innovative potential